Improving the viability and perception of HBCUS - Okpala, Comfort O.; Walker, Kimberly Young (The africana experience and critical leadership studies, 2018)
The book examines HBCUs and their role in higher education through several lenses, including politics, education policy, leadership practice, culture, and social justice. It will guide HBCU leaders and administrators to improve their institutions holistically during the age of accountability.